In vitro–in vivo extrapolation of bexarotene metabolism in the presence of chronic kidney disease and acute kidney injury in rat using physiologically based pharmacokinetic modeling and extrapolation to human - Alsmadi, Mo'tasem M.; Alzughoul, Saja B. (Biopharmaceutics & drug disposition, 2023)
Renal impairment can affect the elimination of hepatically metabolized drugs. Bexarotene (BXT) used for cutaneous T‐cell lymphoma is highly bound in plasma and metabolized by CYP3A4. The BXT European Medicine Agency and Food and Drug Administration packages recommended the evaluation of renal impairment on BXT metabolism. The plasma protein binding of BXT can be changed in patients with renal dysfunction due to hypoalbuminemia and accumulation of uremic toxins. In vitro, microsomal stability and plasma protein binding studies were pursued. A preclinical pharmacokinetic study was pursued in control, chronic kidney disease (CKD), and acute kidney injury (AKI) rats. A BXT physiologically based pharmacokinetic (PBPK) model that utilized in vitro–in vivo extrapolation of metabolism was established and verified in healthy rats, customized to CKD and AKI rats, and extrapolated to healthy human subjects and those with CKD stages 3, 4, and 5. In vitro studies showed that AKI and CKD significantly increased the BXT fraction unbound in plasma (from 0.011 to 0.018 and 0.022, respectively) and decreased intrinsic clearance (from 4.1 to 2.5, and 2.2 mL/min/g liver, respectively). This could explain the reduced in vivo clearance observed in CKD rats (from 0.4 to 0.28 L/h/kg) and the 1.3‐fold increase in BXT exposure. Changes in BXT disposition in AKI rats were not straightforward due to simultaneous changes in BXT distribution. The human PBPK model predicted an increased BXT exposure by 2‐fold in CKD patients, suggesting the need for dose reduction and drug monitoring. The reduced BXT metabolism due to renal impairment is especially relevant in cancer patients with CKD. Renal impairment was associated with increased bexarotene fraction unbound in plasma, decreased in vitro intrinsic clearance, and in vivo total plasma clearance in rats. The human physiologically based pharmacokinetic model predicted an increased bexarotene exposure 1.9–2.1 fold in chronic kidney disease (CKD) stages 3, 4, and 5 compared with cancer patients, which may require dose reduction and drug monitoring, especially in cancer patients suffering from CKD.